Spindlefish and stars - Andrews, Christiane M. (Little, Brown and Company, 2021)
Clothilde has lived a nomadic life with her father, an art restorer and part-time thief. When it's time to leave a village, he typically signals her and they meet to move on to another place. However, one morning, her father doesn't show and she's given a mysterious ticket from a swineherd. Clo, who thinks she'll be reunited with her father, lands on a grey-cast island where she's imprisoned as a slave to an old woman who weaves a living tapestry from fish remains. Clo is desperate to escape but must figure out the mystery of the island and the power of the old woman's tapestry.